Isolation Of Potash Mobilizing Bacteria And Evaluation Of Their Efficacy For Potash Mobilization (Journal of Plant Disease Sciences, 2020)
Potassium is a major and essential macronutrient for normal plant growth and development and it exist in several forms in soil. The present investigation was undertaken to isolate potash mobilizing bacteria from soil and evaluation of their potential in increasing available potash under in vitro. Four potash mobilizing bacteria were isolated from rhizosphere soil samples collected from Ahmednagar, Nashik, Dhule and Sangli districts. The isolates were characterized based on their cultural and morphological characteristics. Among four isolates, KMB-1 and KMB-2 have shown maximum zone of clearance (6.0 mm) and significantly superior in mobilizing soil potassium at 90 DAI (562.5 and 321.5 kg/ha, respectively).
Keywords: Isolation; characterization; potash mobilizing bactertia